Students' Cognitive Analysis using Rasch Modeling as an Assessment for Planning of Strategies in Chemistry Learning - Rusmansyah Rusmansyah; Almubarak Almubarak (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
Rasch modelling based on assessment can help teachers analyze the students' cognitive knowledge level and development. However, teachers are considered unsuccessful in teaching where the achievement of indicators in learning science, such as chemistry, is not holistically actualized. This study aimed to analyze High School students' knowledge in Banjarmasin City, especially on students' knowledge (cognitive aspect), using the Rasch modelling data analysis technique and exploring how chemical learning strategies are planned based on the symptoms of the data obtained. The data collection technique used a dichotomous format test technique (multiple choices). The research method used was descriptive with a quantitative approach to examine Rasch's various data, which was then interpreted qualitatively to describe the issues raised. The study results show that person reliability (students) based on Rasch modelling analysis is +0.79, and item reliability is +0.98, where the value indicates that the consistency of the participant response pattern is